Letter to the Editor Vol.30(3) - Akhter, Neke (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12472 J Bangladesh Coll Phys Surg 2012; 30: 183